An introduction to the Greek New Testament: produced at Tyndale House, Cambridge - Jongkind, Dirk (Crossway, 2019)
This short book offers Greek students answers to crucial questions about The Greek New Testament, Produced at Tyndale House, Cambridge and the Greek New Testament in general.